Win, lose, or draw: determining the winner in sustaining positive public image in the competition between public libraries and electronic media - Vrana, Radovan (Array, 2007)
Today more than ever before, libraries need promotion of their sometimes unrecognized values. The purpose of a library is to act in response to user's information needs by offering content and services. For generations, users kept coming to public libraries, places with central role in providing information resources to general population. At present, as it is widely known and repeated many times over, the Internet may have changed users’ perspective and attitude towards libraries profoundly, especially among the young generations attracted mostly by television and the Internet. Librarians can ask themselves what they or their public library can do to reclaim the role of the primary provider of quality information resources and accompanying services. When compared to television and the Internet, public libraries employ less aggressive advertising campaigns of their products and services. In libraries we usually don’ t recognize brands we are accustomed to in electronic media. Still, libraries put in a great deal of effort to sustain their public image of organizations undoubtedly contributing quality content and services to their users. QoS (Quality of Service) evaluation and research among users and non users about libraries’ public image should offer some indications about public image and recognition of libraries’ promotional efforts in the local community. Many of over 200 public libraries in Croatia currently employ different marketing techniques, including promotion of their holdings and services. Yet, in the age of the Internet, it is probable that they will have to increase their PR (Public Relations) efforts. They already work in partnership with local newspapers and radio stations ; they advertise their services by use of banners on Web sites, invite celebrities to public forums held in their premises, print promotional material like brochures, bookmarks, logos on pens and pencils etc. To establish whether or not promotional efforts help libraries to be more visible and their services recognizable, a survey in selected public libraries in Zagreb (Croatia) was carried out. It is expected that the findings will help librarians in planning new promotional campaigns in public libraries.